Blood Pressure Profile in Post-Stroke Patients - Jahan, Sehelly; Alam, Md Tarek; Masud, Zafor Md; Ali, Zahed (Bangladesh Journal of Neuroscience, 2009)
Blood pressure profile after ischemic stroke in both hypertensive and non-hypertensive patients usually follows a benign course. This prospective study was done among the admitted patients in Bangladesh medical college, starting from November 2006 to August 2007. We observed 80 cases where there was sharp rise of blood pressure in most cases in the early part of ischemic stroke which gradually came down to its previous level within 7-10 days, without any antihypertensive drug. These patients were specially selected as they had only ischemic stroke with or without hypertension. Patients having comorbidities other than diabetes were excluded. DOI: http://dx.doi.org/10.3329/bjn.v24i1.3040 Bangladesh Journal of Neuroscience 2008; Vol. 24 (1) : 45-49